HUBUNGAN TINGKAT PENGETAHUAN ORANG TUA TENTANG VAKSIN COVID-19 DENGAN PELAKSANAAN VAKSINASI COVID-19 PADA ANAK USIA 6-11 TAHUN DI SD SWASTA 1 KLUMPANG - Fauziah Khairunnisa Lubis; Lam Murni Sagala (Indonesian Trust Nursing Journal, 2023)
Covid-19 vaccination is essential in protecting children's health. School age child is vulnerable age to infected disease because the Covid-19 vaccination is important to give toschool age child to increase child’s immunity. The phenomenon that happened is still there are parents who are a level of knowledge still not enough about the vaccine for children 6-11 years old, so that causes refusal to vaccinate their children. The purpose of this study is to knowthe Parent’s Knowledge Level about Covid-19 Vaccination on Child Age 6-11 Years at Klumpang Private Elementary School 1. The research design usedcross sectional. With purposive sampling technique. The Sample of this study this is 75 respondents. Respondent’s Knowledge Level about Covid-19 vaccination on children 6-11 years old is 45 respondents (60%) with good knowledge and 30 respondents (40%) Less knowledge. It concluded that parents with a child aged 6-11 years old at Klumpang Private Elementary School 1 have knowledge levelis not enough about Covid-19 vaccination. The importance for education to increase parental knowledge about the benefit of Covid-19 vaccination through various sources of information so that children can quick get Covid-19 vaccination. Abstrak Vaksinasi Covid-19 merupakan hal penting dalam usaha melindungi Kesehatan anak. Anak usia sekolah merupakan usia yang rentan terinfeksi penyakit, oleh sebab itu vaksinasi Covid-19 sangat penting di berikan kepada anak usia sekolah dengan tujuan meningkatkan imunitas pada anak. Fenomena yang terjadi adalah masih ada orang tua yang tingkat pengetahuannya masih kurang tentang vaksin pada anak usia 611 tahun sehingga menyebabkan adanya penolakan anaknya untuk di vaksin. Tujuan penelitian yaitu mengetahui Tingkat Pengetahuan Orang Tua tentang Vaksinasi Covid-19 pada Anak Usia 6-11 Tahun di SD Swasta PAB 1 Klumpang. Desain penelitian yang digunakan adalah cross sectional dengan teknik purposive sampling. Sampel penelitian ini berjumlah 75 responden. Tingkat Pengetahuan Responden tentang vaksinasi Covid19 pada anak usia 6-11 tahun terdapat 45 responden (60%) pengetahuan baik dan 30 responden (40%) pengetahuan kurang. Disimpulkan bahwa orang tua dengan anak usia sekolah 6-11 tahun di SD Swasta PAB 1 Klumpang memiliki tingkat pengetahuan kurang tentang vaksinasi Covid-19. Pentingnya edukasi untuk meningkatkan pengetahuan orang tua tentang manfaat vaksinasi Covid-19 melalui berbagai sumber informasi sehingga anak bisa segera menerima vaksinasi Covid-19.